2020
DOI: 10.1080/15476286.2020.1724715
|View full text |Cite
|
Sign up to set email alerts
|

RATEmiRs: the rat atlas of tissue-specific and enriched miRNAs for discerning baseline expression exclusivity of candidate biomarkers

Abstract: MicroRNAs (miRNAs) are small RNAs that regulate mRNA expression and have been targeted as biomarkers of organ damage and disease. To explore the utility of miRNAs to assess injury to specific tissues, a tissue atlas of miRNA abundance was constructed. The Rat Atlas of Tissue-specific and Enriched miRNAs (RATEmiRs) catalogues miRNA sequencing data from 21 and 23 tissues in male and female Sprague-Dawley rats, respectively. RATEmiRs identifies tissue-enriched (TE), tissue-specific (TS), or organ-specific (OS) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Some research reported the specific and enriched sites of miRNAs analyzed through the number of miRNAs present in various tissues and organs of rats and humans, which were detected via high-throughput sequencing. Bushel et al ( Bushel et al, 2020 ) constructed a tissue atlas of miRNA abundance with miRNAs sequencing data of tissues in rats. The atlas contains three bioinformatics pipelines to detect abundant miRNAs.…”
Section: The Distribution Of Mirnasmentioning
confidence: 99%
“…Some research reported the specific and enriched sites of miRNAs analyzed through the number of miRNAs present in various tissues and organs of rats and humans, which were detected via high-throughput sequencing. Bushel et al ( Bushel et al, 2020 ) constructed a tissue atlas of miRNA abundance with miRNAs sequencing data of tissues in rats. The atlas contains three bioinformatics pipelines to detect abundant miRNAs.…”
Section: The Distribution Of Mirnasmentioning
confidence: 99%
“…Several previous studies have shown that the X-linked miR-506 family miRNAs are predominantly expressed in the testis of multiple species (15,16,24,(37)(38)(39). By analyzing the publicly available small RNA sequencing (sRNA-seq) datasets from multiple species, including humans, rhesus monkeys, mice, rats, rabbits, dogs, and cows (27,40,41), we further confirmed that miR-506 family miRNAs were indeed highly abundant in the testis, but barely expressed in other organs (Fig. S6, and Table S3).…”
Section: Main Text Introductionmentioning
confidence: 99%